Narasi Konflik dan Fragmentasi Pengetahuan Masa Lalu dalam Pendidikan: Studi Kasus di Kabupaten Pidie, Aceh - Ikramatoun, Siti; Barakah, Fadlan (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
The way past conflict narratives are understood and taught plays a crucial role in reconciliation and peacebuilding efforts in post-conflict regions such as Aceh, Indonesia. However, the effectiveness of this process depends on how complex and sensitive historical knowledge is transmitted and internalized by key educational actors. This study aims to examine the depth, sources, and characteristics of historical knowledge about the Aceh conflict held by high school teachers and students in Pidie District. Employing a qualitative descriptive method, data were collected through in-depth interviews, passive classroom observation, and document analysis at MAN 1 Pidie. The findings reveal a significant knowledge gap. Teachers’ understanding of the Aceh conflict tends to be fragmented, heavily reliant on personal experiences, and constrained by perceptions of limited formal teaching resources. As a result, students acquire minimal formal knowledge from school, often relying on informal sources—such as family narratives and digital media—whose validity is questionable. This knowledge gap hinders the development of students’ critical understanding of the past and limits the potential of education as a transformative vehicle for peace. The study underscores the urgent need for systemic interventions, including curriculum reform, foundational capacity-building for teachers (content mastery and critical pedagogy), and the enhancement of students’ critical literacy in navigating contested historical narratives. Abstrak Bagaimana narasi konflik masa lalu dipahami dan diajarkan memainkan peran krusial dalam proses rekonsiliasi dan pembangunan perdamaian di wilayah pasca-konflik seperti Aceh, Indonesia. Namun, efektivitasnya bergantung pada bagaimana pengetahuan tentang masa lalu yang kompleks dan sensitif ditransmisikan dan dipahami oleh aktor kunci dalam sistem pendidikan. Penelitian ini bertujuan menganalisis kedalaman, sumber, dan karakteristik pengetahuan guru dan siswa sekolah menengah atas di Kabupaten Pidie mengenai narasi konflik Aceh. Menggunakan metode kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam, observasi kelas partisipan pasif, dan analisis dokumen di MAN 1 Pidie, melibatkan guru mata pelajaran relevan (Sejarah, Sosiologi, PKN) dan siswa jurusan IPS. Hasil penelitian menunjukkan adanya kesenjangan pengetahuan yang signifikan. Pengetahuan guru mengenai narasi konflik Aceh cenderung fragmentaris, sangat bergantung pada pengalaman personal, dan terkendala persepsi keterbatasan sumber ajar formal. Akibatnya, pengetahuan siswa yang diperoleh dari sekolah sangat minimal, mendorong mereka bergantung pada sumber informasi informal (narasi keluarga, media digital) yang validitasnya diragukan. Kesenjangan ini menghambat pembentukan pemahaman kritis mengenai masa lalu (critical understanding of the past) dan efektivitas pendidikan untuk perdamaian. Studi ini menegaskan perlunya intervensi sistemik yang mencakup reformasi kurikulum, penguatan kapasitas fundamental guru (penguasaan materi & pedagogi kritis), serta pengembangan literasi kritis siswa dalam menavigasi narasi masa lalu.